Une histoire sociolinguistique de la possession d’Aix-en-Provence (1610-1611) - Jean-Pierre Cavaillé; Sophie Houdard (Etudes Epistémè)
In an important case of possession from early 17th-century France (also called the affair of Gaufridy or of Madeleine de Demandols), the devils are extremely loquacious. The figure of the preaching devil is preeminent. This contribution will first describe the circumstances and the context of this famous case and discuss the texts that publicized it (most importantly the Histoire admirable of the exorcists Sébastien Michaelis and François Dooms). It will then focus on the question of the linguistic skills and limits of the devils. First of all, there is the fact that knowing languages that one had not learned (here, Latin) was considered a major sign of possession, but this was also heavily disputed and at the heart of the controversies that agitated this case, which might be considered exemplary for many reasons. On the other hand, there is the important fact, even if it was concealed by the contemporary apologetic literature and French historiography, that the devils of Aix spoke mainly Provençal Occitan, as did all the other protagonists. This article is largely dedicated to the sociolinguistic analysis of the languages in use: Provençal, French, and Latin, as well as to the question of the cultural, social, and gendered identities of the actors in this case of possession and in the trial: the judges, the exorcists, the possessed, and the popular and educated audience of the exorcisms.